Soil persistence and infection capacity of Fusarium moniliforme var. subglutinans - Matos, Aristóteles Pires de; Cunha, Getulio Augusto Pinto da (Pesquisa Agropecuaria Brasileira, 2014)
The persistence os Fusarium moniliforme var. subglutinans was avaluated in sterilized and non-sterilized soils. The pathogen infection capacity was measured on slips of pineapple 'Perola'. The fungus persistence was longer in sterilized soil than in non sterilized one. The slips were infected by the pathogen only when planted just after soil contamination and with their leaves removed.